Do informalismo à rarefação: La mala vida, de Salvador Garmendia e Hotel Atlântico, de João Gilberto Noll - Ferigolo, Ivana (2006)
This work aims at verifying through the analysis of the novels La mala vida, by Venezuelan writer Salvador Garmendia, and Hotel Atlântico, from Brazilian João Gilberto Noll, which are the possible structural and thematic changes the novel has been going through in order to represent contemporary human experiences. To do so, the analysis parameters were the narrator-character category and the time-space coordinates, as well as the relationship between the novel s characters, those two parameters and the other characters in the stories. The analysis made suggest the novel has been going through a transformation process, which meets the progressive diminishing of the representation of an experience, which is registered in La mala vida and is very highlighted in Hotel Atlântico. This happens because in the La mala vida the experience figures through the existential fragments inherent to the narrator s life, while in the Hotel Atlântico novel, the experience is non-existent because the protagonist cannot convert its experiences. Thus, it is concluded that, in order to represent contemporary social and human practices, the novel seems to abdicate its main component, the representation of an experience, and consequently it does not tend to have a role in human existence.